A Review of the Evidence for Melanoma in Nine Inca Mummies. (3rd April 2017) - Mark, S.
Abstract: An often cited statement in the medical literature is that nine Inca mummies (c.400 bc ) had skin and osseous lesions from melanoma. However, a review of the pattern and type of osseous lesions exhibited by these individuals and the age of at least one of them indicate the data are inconsistent with a diagnosis of melanoma. Copyright © 2017 John Wiley & Sons, Ltd.